Fiscal Vulnerabilities and Risks from Local Government Finance in China - Zhang, Yuanyan (IMF Working Papers; Working Paper, 2014)
China weathered the global financial crisis better than most, thanks to a large and timely stimulus. This stimulus, however, was mainly in the form of off-budget infrastructure spending and thus not visible in the headline fiscal data. We construct a time series for the augmented fiscal deficit and debt-augmented to include off-budget activity-that better illustrates the counter-cyclical role of fiscal policy. The results also show that the augmented fiscal deficit and debt are both considerably higher than the headline government data suggest. Nonetheless, at around 45 percent of GDP, the augmented debt is still at a manageable level.